2017
DOI: 10.1016/j.dib.2017.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Microarray dataset of transgenic rice overexpressing Abp57

Abstract: The dataset presented in this article describes microarray experiment of Auxin-binding protein 57, Abp57-overexpressing transgenic rice. The gene expression profiles were generated using Affymetrix GeneChip® Rice (Cn) Gene 1.0 ST Arrays. Total RNA from seedlings tissue of transgenic rice and wildtype, which serve as control were used as starting materials for microarray experiment. Detailed experimental methods and data analysis were described here. The raw and normalized microarray data were deposited into Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that transgenic rice harbour stress-related genes such as NHX1 (vacuolar Na + /H + antiporter) [ 276 ], ADC (arginine decarboxylase) [ 277 ], Calcineurin , CBF3 (C-repeat element binding factor 3) [ 278 ], codA (choline oxidase) [ 279 ], HVA1 (LEA protein) [ 280 ], OsCDPK7 (regulatory factor) [ 49 ], OsMAPK5 (mitogen-activated protein kinase) [ 281 ], SOD2 (plasma membrane Na + /H + antiporter) [ 282 ] and TPSP (trehalose-6-phosphate synthase and phosphatase) [ 283 ] to enhance abiotic stress tolerance, especially salinity and drought. A recent study also found that the overexpression salt-responsive gene OsPP1a [ 284 ], OsASR1 [ 285 ], Abp57 [ 286 ], SIDP361 [ 287 ], OsSUV3 [ 288 ] and PDH45 [ 289 ] contribute to salinity tolerance in rice. As seen above, significant progress has been achieved in improving abiotic-stress-tolerant transgenic rice.…”
Section: Modernise Breeding Approaches For Rice Salinity Improvementmentioning
confidence: 99%
“…Previous studies demonstrated that transgenic rice harbour stress-related genes such as NHX1 (vacuolar Na + /H + antiporter) [ 276 ], ADC (arginine decarboxylase) [ 277 ], Calcineurin , CBF3 (C-repeat element binding factor 3) [ 278 ], codA (choline oxidase) [ 279 ], HVA1 (LEA protein) [ 280 ], OsCDPK7 (regulatory factor) [ 49 ], OsMAPK5 (mitogen-activated protein kinase) [ 281 ], SOD2 (plasma membrane Na + /H + antiporter) [ 282 ] and TPSP (trehalose-6-phosphate synthase and phosphatase) [ 283 ] to enhance abiotic stress tolerance, especially salinity and drought. A recent study also found that the overexpression salt-responsive gene OsPP1a [ 284 ], OsASR1 [ 285 ], Abp57 [ 286 ], SIDP361 [ 287 ], OsSUV3 [ 288 ] and PDH45 [ 289 ] contribute to salinity tolerance in rice. As seen above, significant progress has been achieved in improving abiotic-stress-tolerant transgenic rice.…”
Section: Modernise Breeding Approaches For Rice Salinity Improvementmentioning
confidence: 99%
“…The robust multiarray analysis (RMA) method was applied to ensure that the relative log expression signal (RLE) was comparable between samples. The microarray experiment was then previously deposited into the NCBI by [21] and is accessible through the NCBI GEO DataSets (DOI: https:// www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE99055, accessed on 1 June 2017) [22].…”
Section: Gene Expression Profiling Differentially Expressed Genes (De...mentioning
confidence: 99%
“…To further support the reliability of our Abp57-OE microarray data in drought, the coexpression module analysis was carried out using the CEMiTool R package version 1.20 [30]. The published microarray dataset, under the accession number GSE99055, was employed as a discovery set [21]. In this study, the correlation method of Pearson was selected to transform the gene expression matrix (m × n) into an adjacency matrix, where m denotes as genes and n represents the samples.…”
Section: Construction Of Gene Co-expression Network Modulesmentioning
confidence: 99%